PENGARUH INOVASI PRODUK DAN KINERJA PEMASARAN TERHADAP KEUNGGULAN BERSAING UMKM DI PIA KUKUS MADE BALI - Putu Jeje Surat Diantara; Wayan Ardani; Putu Ari Mulyani (Jurnal Ilmiah Satyagraha, 2025)
This study aims (1) to determine the effect of product innovation and oncompetitive advantage in Pia Kukus Made Bali MSMEs; (2) to determine the effect ofmarketing performance on competitive advantage in Pia Kukus Made Bali MSMEs; and (3)to determine the effect of product innovation and marketing performance simultaneously oncompetitive advantage in Pia Kukus Made Bali MSMEs. This research is a research withcausal quantitative methods. The subjects in this study, namely Pia Kukus Made Baliconsumers and the objects of this research include product innovation, marketingperformance, and competitive advantage. In this study using a sample of 100 respondentswho are consumers of Made Bali Steamed Pia. The data source is primary data collectedthrough questionnaires. The data analysis used is validity test, reliability test, classical assumption test, t test, F test, and coefficient of determination test using SPSS 25. The resultsof this study are: (1) Product innovation has a positive and significant effect on thecompetitive advantage of MSMEs; (2) Marketing performance has a positive and significanteffect on the competitive advantage of; (3) Product innovation and marketing performancetogether have a positive and significant effect on the competitive advantage of MSMEs.